2014
DOI: 10.1371/journal.pone.0111629
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Impacts of Genetically Modified Crops

Abstract: BackgroundDespite the rapid adoption of genetically modified (GM) crops by farmers in many countries, controversies about this technology continue. Uncertainty about GM crop impacts is one reason for widespread public suspicion.ObjectiveWe carry out a meta-analysis of the agronomic and economic impacts of GM crops to consolidate the evidence.Data SourcesOriginal studies for inclusion were identified through keyword searches in ISI Web of Knowledge, Google Scholar, EconLit, and AgEcon Search.Study Eligibility C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
395
2
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 692 publications
(418 citation statements)
references
References 21 publications
11
395
2
10
Order By: Relevance
“…The literature reviewed here (99 papers) was dominated by studies of economic impact. That this trend goes beyond our review is illustrated by a recent meta-analysis published by Klümper and Qaim [8], which initially indicated that it would take a broad approach to social impact but then focused only on economic impacts (specifically impacts on crop yield, pesticide quantity, pesticide cost, total production cost and farm profits). The belief that social impacts can be measured by only addressing economic aspects has resulted in a general past trend of measuring social progress only in economic terms [103].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The literature reviewed here (99 papers) was dominated by studies of economic impact. That this trend goes beyond our review is illustrated by a recent meta-analysis published by Klümper and Qaim [8], which initially indicated that it would take a broad approach to social impact but then focused only on economic impacts (specifically impacts on crop yield, pesticide quantity, pesticide cost, total production cost and farm profits). The belief that social impacts can be measured by only addressing economic aspects has resulted in a general past trend of measuring social progress only in economic terms [103].…”
Section: Resultsmentioning
confidence: 98%
“…Previous discussions and evaluations of sustainability in general [4][5][6] and of agricultural practices [7] have been dominated by the ecological dimension, whereas the social aspects of sustainability have been rather neglected. However, the social impacts of GM crops in agriculture have been discussed in numerous studies (e.g., [8,9]). The sustainability-focused research on GM crops might thus be at the forefront of research addressing the social dimension of sustainability in agriculture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Therefore, the rejection of GMOs based on consensus approximations might turn out to be detrimental to most of humanity within a few decades. 19 If we accept scientific evidence that GMOs are not more harmful to human health than their non-GM equivalents, and if we accept GMOs' gains in yield and in pest resistance (e.g., Klümper and Qaim, 2014), public opposition to GMOs creates social gridlocks. These gridlocks happen when the conditions of agents (e.g., consumers, farmers) could be improved without worsening the condition of anyone else (or, at least, without worsening the condition of another agent in proportions larger than would have been the case with non-GMOs).…”
Section: Second Best and Political Legitimacymentioning
confidence: 99%
“…Recent studies indicate the cultivation of transgenic plants benefits both farmers as well as the environment. 1,2 Many bioengineered plants are created through random insertion of transgenes that include a marker gene for selection of transgenic cells from non-transformed tissues. Some regions of the world are resistant to growing bioengineered plants for a number of reasons.…”
Section: Abstract Chimeric Transposase; Insect Transposon; Plants; Simentioning
confidence: 99%